The legacy of Ludwig von Bertalanffy and its relevance for our time. (29th April 2019) - Hammond, Debora
Abstract : This paper provides a brief overview of Ludwig von Bertalanffy's contributions to the evolution of the fields of biology and systems theory and the significance of his work in relation to contemporary developments across a broad spectrum of disciplines. In documenting some of the ways in which his insights have remained relevant, inspiring scholars and practitioners in a variety of fields, it also addresses the philosophical and ethical implications inherent in Bertalanffy's work. Perhaps one of the most striking dimensions of his writing is his passionate critique of mechanistic science, which he sees as dehumanizing and as responsible for many of the challenges confronting humanity. In contrast, he emphasized the humanistic orientation of his conception of general systems theory as an approach that could provide guidelines and support for addressing these challenges.